Strategi Guru dalam Menanamkan Nilai Akidah dan Akhlak pada Siswa Madrasah Ibtidaiyah: Studi di MI Ridogalih - Rahmat, Mamat; Rohmatin, Alfa; Pujiawaati Pujiawaati; Adelia Sapitri; Siti Rohilah; Paoz Mutaqin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to outline how aqeedah and moral values are applied in the learning process of fourth-grade students at MI Ridogalih, examine the strategies teachers use to internalize these values, and identify factors that support or hinder the process. Using a descriptive qualitative method, the research gathered data from the Aqeedah–Akhlaq teacher, instructional documents, and records of the school’s religious activities. Data collection was conducted through guided interviews and document review, and the analysis followed the Miles and Huberman interactive model. The results show that the incorporation of aqeedah and moral education is implemented through consistent religious habituation, exemplary behavior demonstrated by teachers, and the integration of Islamic principles into classroom instruction. Contributing factors include the strong religious environment of the school and active parental engagement, while obstacles stem from the influence of digital media and the varied backgrounds of students’ families. The study concludes that combining habituation practices, teacher role modeling, and value integration plays a significant role in reinforcing students’ Islamic character development.